Ethics for a Broken World : Imagining Philosophy After Catastrophe. - Mulgan, Tim (Taylor and Francis, 2014)
Imagine living in the future in a world already damaged by humankind, a world where resources are insufficient to meet everyone''s basic needs and where a chaotic climate makes life precarious. Then imagine looking back into the past, back to our own time and assessing the ethics of the early twenty-first century. ""Ethics for a Broken World"" imagines how the future might judge us and how living in a time of global environmental degradation might utterly reshape the politics and ethics of the future. This book is presented as a series of history of philosophy lectures given in the future, stu